Resettling the borderlands : state relocations and ethnic conflict in the South Caucasus - Shafiyev, Farid, 1969- (McGill-Queen's University Press, 2018)
A study of Imperial Russian and Soviet resettlement policies in the South Caucasus and their impact on the ethnic conflict.